The strengthening effect of inter-layer cold working and post-deposition heat treatment on the additively manufactured Al-6.3Cu alloy - Gu, Jianglong; Ding, Jialuo; Williams, Stewart W.; Gu, Huimin; Bai, Jing; Zhai, Yuchun; Ma, Peihua (Elsevier, 2015)
Wire + Arc Additive Manufacture (WAAM) attracts great interest from the aerospace industry for producing components with aluminum alloys, particularly Al-Cu alloy of the 2000 series such as 2219 alloy. However the application is restricted by the low strength properties of the as-deposited WAAM metal. In this study two strengthening methods were investigated - inter-layer cold working and post-deposition heat treatment. Straight wall samples were prepared with 2319 aluminum alloy wire. Inter-layer rolling with loads of 15 kN, 30 kN and 45 kN were employed during deposition. The ultimate tensile strength (UTS) and yield strength (YS) of the inter-layer rolled alloy with 45 kN load can achieve 314. MPa and 244. MPa respectively. The influence of post-deposition T6 heat treatment was investigated on the WAAM alloy with or without rolling. Compared with inter-layer rolling, post-deposition heat treatment can provide much greater enhancement of the strength. After T6 treatment, the UTS and YS of both of the as-deposited and 45 kN rolled alloys exceeded 450. MPa and 305. MPa respectively, which are higher than the properties of the wrought 2219-T6 alloy. The strengthening mechanisms of this additively manufactured Al-6.3Cu alloy were investigated through microstructure analysis.
Keywords: Aluminum alloy; Heat treatment; High strength; Wire + Arc Additive Manufacture (WAAM); High strength; Rolling